2021
DOI: 10.3389/fphar.2021.744085
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Survivors Suffering From Sensory Chemotherapy-Induced Peripheral Neuropathy Are Not a Homogenous Group: Secondary Analysis of Patients’ Profiles With Oxaliplatin-Induced Peripheral Neuropathy

Abstract: Oxaliplatin, a pivotal drug in the management of colorectal cancer, causes chemotherapy-induced peripheral neuropathy (CIPN) in a third of cancer survivors. Based on a previous cross-sectional study assessing oxaliplatin-related sensory CIPN in colorectal cancer survivors, a secondary analysis was designed to explore the possibility that different clusters of patients may co-exist among a cohort of patients with oxaliplatin-related CIPN. Other objectives were to characterize these clusters considering CIPN sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Although several studies have previously examined the relationship between BMI and OIPN in CRC, they have reported conflicting findings. One retrospective investigation 6 observed an inverse relationship between BMI and OIPN; however, four prospective studies [7][8][9][10] of approximately 100 patients with CRC each reported a positive correlation. In our significantly larger cohort, we similarly demonstrate that a higher BMI is associated with increased severity of CTCAEreported-although not FACT/GOG-NTX-13-measuredneuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies have previously examined the relationship between BMI and OIPN in CRC, they have reported conflicting findings. One retrospective investigation 6 observed an inverse relationship between BMI and OIPN; however, four prospective studies [7][8][9][10] of approximately 100 patients with CRC each reported a positive correlation. In our significantly larger cohort, we similarly demonstrate that a higher BMI is associated with increased severity of CTCAEreported-although not FACT/GOG-NTX-13-measuredneuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% of patients with CRC treated with oxaliplatin may develop OIPN, 52 resulting in impairments in daily functioning, mental health, and quality of life. 8,[53][54][55] As patients with CRC comprise one of the largest groups of cancer survivors, 56 improving our understanding of preventing and managing chronic OIPN is of especially high importance. Shorter chemotherapy durations in the management of CRC have been shown to be similarly effective as longer treatments, 22,23,57 and our findings lend support for potential additional benefits through decreased chemotherapy-related toxicity and improved treatment adherence and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome used to assess and validate CIPN in animals was the presence of nociceptive disorders, specifically tactile allodynia thresholds assessed using the electronic von Frey test. Neuropathic pain serves as a reliable marker of CIPN severity in patients [ 3 , 4 , 58 ]. Measuring nociceptive thresholds in living rodents is convenient and allows for repeatability [ 59 ].…”
Section: Discussionmentioning
confidence: 99%